1962
DOI: 10.1029/jz067i005p01795
|View full text |Cite
|
Sign up to set email alerts
|

On the altitude at which some solar-flare-induced lonization is released

Abstract: During the occurrence of certain solar flares and subflares (about 20 to 25 per cent of those optically observed), the instantaneous frequency of a highly stable, CW, HF signal transmitted obliquely through the ionosphere, over distances of the order of 5000 km, is momentarily changed by a few cycles. The change consists of an increase in the frequency, followed by a decrease and, subsequently, a gradual return toward the original received frequency. The rapidly changing portion of the frequency variation last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1965
1965
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…An atmospheric model specifying electron collision frequency (v) as a function of height can then be used to locate the "slab" of ionization assumed responsible for both effects. Similar work has been carried out by Kanellakos, Chan, and Villard [1962]. These studies have helped to establish the fact that solar-flare effects are relatively frequent at heights above the D region of the ionosphere Davies [1962c] has also shown that the Doppler technique can he used for study of ionospheric drifts.…”
mentioning
confidence: 59%
“…An atmospheric model specifying electron collision frequency (v) as a function of height can then be used to locate the "slab" of ionization assumed responsible for both effects. Similar work has been carried out by Kanellakos, Chan, and Villard [1962]. These studies have helped to establish the fact that solar-flare effects are relatively frequent at heights above the D region of the ionosphere Davies [1962c] has also shown that the Doppler technique can he used for study of ionospheric drifts.…”
mentioning
confidence: 59%
“…These disturbances may be the result either of atmospheric waves [36] or of additional ionization [37], [38]. CW, H F transmissions over long paths, using one or more ionospheric reflections, may be used.…”
Section: H F (Forward P R O P~g a T I O N )~mentioning
confidence: 99%
“…The nuclear-induced effects discussed in the last section may also be detected by H F sounders of various types [38]. Sounders which record the change of phase or the rate of change of phase on a fast time base are particularly useful.…”
Section: Radio Soundersmentioning
confidence: 99%
“…The low latitudes showed a larger increase in the TEC compared with the high latitude. Some events of solar flares have also been studied by Kanellakos et al (1962) to see the effect on the E-and F-region ionosphere and it has been found that the electron density was enhanced at these heights. Thome and Wagner (1971) effect of soar flares on electron density and found that the electron density is enhanced in the E-and F-regions of the ionosphere.…”
Section: Introductionmentioning
confidence: 99%